2023
DOI: 10.7554/elife.84899
|View full text |Cite
|
Sign up to set email alerts
|

The natural tannins oligomeric proanthocyanidins and punicalagin are potent inhibitors of infection by SARS-CoV-2

Hsiao-Fan Chen,
Wei-Jan Wang,
Chung-Yu Chen
et al.

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic continues to infect people worldwide. While the vaccinated population has been increasing, the rising breakthrough infection persists in the vaccinated population. For living with the virus, the dietary guidelines to prevent virus infection are worthy of and timely to develop further. Tannic acid has been demonstrated to be an effective inhibitor of coronavirus and is under clinical trial. Here we found that two other members of the tannins family, oligomeric pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Compounds with a toxicity rate of over 50% were eliminated, while others were subjected to infection using a VPP assay to assess their ability to reduce infection rates (Figure 2B). To further examine the efficiency of our VPP assay, we also used well-known inhibitors, hydroxychloroquine (HCQ) and oligomeric proanthocyanidins (OPCs), as positive controls (Supplementary Figure S1A) [31][32][33]. Several studies have reported that high expression levels of ACE2 are correlated with severe infection and COVID-19-related complications [34,35].…”
Section: Reduced Infection Rates Post-drug Treatment With Dauricine A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds with a toxicity rate of over 50% were eliminated, while others were subjected to infection using a VPP assay to assess their ability to reduce infection rates (Figure 2B). To further examine the efficiency of our VPP assay, we also used well-known inhibitors, hydroxychloroquine (HCQ) and oligomeric proanthocyanidins (OPCs), as positive controls (Supplementary Figure S1A) [31][32][33]. Several studies have reported that high expression levels of ACE2 are correlated with severe infection and COVID-19-related complications [34,35].…”
Section: Reduced Infection Rates Post-drug Treatment With Dauricine A...mentioning
confidence: 99%
“…The data revealed that neither Dauricine nor Isoliensinine possessed any notable effect on TMPRSS2 protease activity (Figure 6C,D) when TMPRSS2 was overexpressed in 293T cells (Supplementary Figure S3B). To further examine the effects of Dauricine and Isoliensinine on TMPRSS2 protease activity, we also used well-known TMPRSS2 inhibitors, tannic acid and oligomeric proanthocyanidins (OPCs), as positive controls (Supplementary Figure S3A) [32,40]. To further analyze the effects of Dauricine and Isoliensinine on infection rates in the presence or absence of TMPRSS2, human TMPRSS2 and a control vector were ectopically expressed in 293T-ACE2 and VeroE6 cell lines (Supplementary Figure S3C,D).…”
Section: Dauricine and Isoliensinine Obstruct Spike Protein-ace2 Inte...mentioning
confidence: 99%
“…-based enzyme activity assay of M pro ; Surface plasmon resonance analysis; Molecular docking; Vpp pseudoviral particle infection assay Dual inhibition of TMPRSS2 and M pro /3CL pro with subsequent SARS-CoV-2 activity inhibition [94,95] Docking characterization and in vitro Inhibitory activity Dual inhibition of TMPRSS2 and M pro /3CL pro with suppression of cellular entry of the virus [94]High potential for SARS-CoV-2 inhibition[96][97][98][99] …”
mentioning
confidence: 99%